Management of coconut eriophyid mite aceria guerreronis keifer using ecofriendly methods - Amritha V S (Department of Agricultural Entomology, College of Agriculture, 2001)
Experiments were conducted in the Department of Agricultural Entomology and in the Instructional Farm, College of Agriculture, Vellayani during 2000-2001, to generate eco-friendly components in developing a sustainable long term strategy of pest management against coconut eriophyid mite. The treatments included the laboratory screerung of various oils, botanicals and synthetic acaricides. The promising treatments and innovative farmer practices were evaluated in a field experiment. The results of laboratory screening revealed that Neem oil three per cent followed by Neemazal 0.4 per cent and castor oil three per cent were promising among the botanicals while fenazaquin 0.05 per cent followed by sulphur W.P 0.4 per cent were found to be effective among the synthetic acaricides. The field evaluation using promising natural products and synthetic acaricides, showed that fenazaquin 0.05 per cent was effective followed by sulphur W.P 0.4 per cent. Maximum protection was observed after the third round of spraying. Sprays applied at the critical stage of infestation afforded maximum protection to the bunches.